Impact of Covid-19 on maximal oxygen uptake, physical activity, and fatigue in Saudi recreational athletes: A cross-sectional study - Aldossari, Hind; Alsubaiei, Mohammed; Shanb, Alsayed; Al Humoud, Shoug; Aldossari, Hail (Acta Biomedica Atenei Parmensis, 2025)
Background: Coronavirus is a novel viral infection that emerged in late 2019. The World Health Organisation declared it a pandemic and life-threatening illness due to its detrimental impacts on multiple organ systems. OObjective: Investigate the long-term impact of Covid-19 on maximal oxygen uptake, physical activity, and fatigue in Saudi recreational athletes.Methods: A total of 42 Saudi male and female recreational athletes participated in a cross-sectional study. They were equally and non-randomly assigned to either an experimental group (21 athletes with a history of Covid-19 infection) or a matched control group (21 healthy athletes). VO2 max, physical activity, and fatigue were measured using the COSMED Quark cardiopulmonary exercise test (CPET) system, the International Physical Activity Questionnaire (IPAQ), and a hand-held blood analyser, respectively. Independent t-test and Mann-Whitney test were used to assess significant differences between the two groups.Results: Significant reductions were observed in mean values of V̇O2 max (40.88 ± 12.94 & 50.16 ± 1.72; d = 0.75; p = 0.019), physical activity (6.81 ± 1.36&7.90 ± 0.89; d = 0.49; p = 0.006), and metabolic equivalents (12.19 ± 3.01&14.5 ± 3.39; d = 0.36; p = 0.025), in contrast, no significant differences were found in mean values for lactic acid (13.91 ± 7.44 &16.33 ± 5.44 ; d = - 0.37; p = 0.473) or respiratory quotient (1.01 ± 0.15&0.95 ± 0.07; d = - 0.27; p = 0.512) in the Covid-19 & matched control groups respectively.Conclusion: Covid-19 was associated with significant reductions in VO2 max, physical activity, and metabolic equivalents among Saudi recreational athletes compared to healthy controls. However, no significant differences were found in mean values of lactic acid or respiratory quotient. Health care providers are advised to prescribe individualised rehabilitative tailored programmes for recreational athletes with Covid-19, regardless of the time since infection.